ANALISIS KANDUNGAN TOTAL LOGAM (Pb), (Fe) DAN PROTEIN PADA KERANG DARAH (Anadaragranosa L) DARI PESISIR LAUT KENYAMUKAN SANGATTA KALIMANTAN TIMUR - Edman Tandirerung; Rudi Kartika; Noor Hindryawati (PROSIDING SEMINAR KIMIA, 2017)
The Research on"Analysis of the total content of Pb, Fe and protein in the blood clams (Anadara granosa L) from sea coast of Kenyamukan Sangatta in East Kalimantan" .Penelitian aims to determine the total content of Pb, Fe and shellfish proteins in the blood clams by the size and location of different sampling. Then the total content of Pb, Fe and protein correlated using Least Square method. The total content analysis of Pb, Fe using AAS (Atomic Absorption Spectrophotometer) and analysis of protein content using the Kjeldahl method. In this study, the total content of Pb, Fe on the location of Pier Oil and Gas companies with an average of 0.805, 1,684 mg / L, general Piers in Kenyamukan 0885, 1,849 mg / L, at Pier coal port 0813, 1,792 mg / L. The protein content of blood clams on the location of Pier Oil and Gas Company with an average of 20.8981%, general Piers in Kenyamukan obtained an average protein content of 23.7947% and Pier coal companies earned an average protein content of 23.4533%. Correlation of the total content of Pb, Fe against the protein content in blood clams (Anadara granosa L) r= 0.8176, r = 0.9066. Keywords: Blood clams (Anadara granosa L), Metal Pb, Fe, Protein